Sustainable supply chain practices and business performance of culinary MSMEs in West Java - Fauzan, Tribowo Rachmat; Sudrajat, Ajeung Syilva Syara Noor Silmi (Journal of Management and Digital Business, 2025)
This study explores the relationship between sustainable supply chain practices and the business performance of Culinary MSMEs in West Java, Indonesia. Using a quantitative approach, data were gathered from 292 Culinary MSMEs through structured questionnaires and analyzed using SEM-PLS with SmartPLS software. The research examines three dimensions of sustainable practices—environmental, social, and economic—and their impact on MSME performance. Findings show that sustainable supply chain practices positively and significantly influence business performance by enhancing operational efficiency, customer satisfaction, and market reputation. The study provides empirical evidence from a developing country context and emphasizes the strategic importance of sustainability for MSMEs aiming to remain competitive and resource-efficient while addressing environmental and social challenges. It also highlights the role of policymakers and supply chain stakeholders in supporting sustainability integration within MSME operations. The study recommends future research to consider longitudinal or comparative approaches across regions to deepen insights into sustainable food supply chain practices.